Differential Equations with Absolutely Unstable Trivial Solutions - Slyusarchuk, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We obtain conditions for the absolute instability of trivial solutions of the nonlinear differential equations.